MOTIONS BY INERTIA AND THE COULOMB FIELD - Oleinik, V. P. (Одеські астрономічні публікації, 2012)
It is proved that there exist accelerated motions by inertia which dropped out of the field of view of classical mechanics. The Coulomb law is not shown to be a universal and fundamental law of physics. Universal formula for the force of interaction between two particles does not exist.